UR_GERICHTE 2015_OG Z 14 25. vom 26. November 2015 - UR Obergericht (2015)
Zivilprozessordnung. Art. 122 Abs. 1 lit. a und Abs. 2, Art. 320 lit. a ZPO. Art. 18 Abs. 2, Art. 19 Abs. 1, Art. 26 Abs. 2 Gerichtsgebührenverordnung.